School Meal Programs in Africa: Regional Results From the 2019 Global Survey of School Meal Programs - Wineman, Ayala; Ekwueme, Moses C.; Bigayimpunzi, Liliane; Martin-Daihirou, Alice; de Gois V. N. Rodrigues, Eth Ludmilla; Etuge, Priscilia; Warner, Yale; Kessler, Heidi; Mitchell, Arlene (Frontiers in Public Health, 2022)
Introduction School meal programs operate throughout Africa, serving as a social safety net and aiming to improve children's nutrition, influence their dietary choices, and strengthen the agrifood economy through local procurement. Despite their rapid expansion in the past decade, there has been no systematic effort to comprehensively document school feeding activities across the continent. Methods Detailed information on school feeding activities in each country was captured in the Global Survey of School Meal Programs©, which launched in 2019. An invitation to participate was extended to each government, which appointed a national-level respondent to gather information on every large-scale school meal program in the country. Results Forty-one countries in Africa (38 in sub-Saharan Africa) responded to the survey in 2019 with information on 68 large-scale programs that together reached 60.1 million children. Across these countries, the aggregate school feeding budget was USD 1.3 billion. Diversity in school meal programs is evident across regions, country income levels, and levels of national commitment. Coverage rates tended to be highest in southern Africa, in countries with school feeding as a line item in the national budget, and in countries with the greatest domestic share of the school feeding budget. Diversity in the school menu tended to be greatest in programs that sourced food through domestic purchase rather than relying on foreign in-kind donations. To address micronutrient malnutrition, about two-thirds of the programs served fortified foods, and one-quarter included micronutrient supplements. Even as rates of overweight/obesity are rising among African school children, just 10% of school meal programs identified its prevention as an objective. Conclusion The extent to which school meal programs in Africa are supported with domestic funding reflects a dramatic shift in favor of national ownership and domestic food procurement. At the same time, programs have grappled with inadequate and unpredictable budgets and challenges related to supply chains and logistics—impediments that need to be addressed if these programs are to achieve their objectives. Overall, the survey results underscore the important position of school meal programs within African food systems and their potential (if well-designed) to sustainably improve food security, child health, and nutrition.